Integrasi Kebijakan dan Partisipasi Publik dalam Rapat Koordinasi Penyediaan Angkutan Umum di Provinsi Sulawesi Tenggara - Sylsiani Mursalim; Galih Adi Sulistyo; Syaiful Syaiful; Ringo Taufan Laode; Rina Sutriana; Maudhy Satyadharma (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
This study aims to analyze policy integration and the level of public participation in the implementation of coordination meetings on public transportation provision in Southeast Sulawesi Province as a strategic effort to improve the quality of land transportation services. This coordination meeting was held on December 3, 2025, involving various stakeholders, including the Southeast Sulawesi Provincial Transportation Agency, the Regency/City Transportation Agency throughout Southeast Sulawesi, Perum DAMRI, and the Passenger Transportation Legal Entity. The research method used was descriptive qualitative with a policy and institutional analysis approach, supported by data from discussions, meeting minutes, and related policy documents. The results showed that the coordination meeting activities were able to strengthen policy understanding between agencies, increase the effectiveness of institutional coordination, and encourage synergy between the role of the government and transportation business actors. In addition, this forum also played a significant role in formulating joint strategies to improve the quality of public transportation services, including aspects of route planning, service standards, and operational sustainability. Through a structured coordination mechanism and discussion, each party gained a more comprehensive understanding of their respective roles, authorities, and responsibilities in the implementation of regional transportation. Thus, this coordination meeting is an important instrument in supporting collaborative and public service-oriented transportation governance.